2012
DOI: 10.1088/0029-5515/52/9/094003
|View full text |Cite
|
Sign up to set email alerts
|

Simulation and theory of spontaneous TAE frequency sweeping

Abstract: A simulation model, based on the linear tip model of Rosenbluth, Berk and Van Dam (RBV), is developed to study frequency sweeping of toroidal Alfvén eigenmodes (TAEs). The time response of the background wave in the RBV model is given by a Volterra integral equation. This model captures the properties of TAE waves both in the gap and in the continuum. The simulation shows that phase space structures form spontaneously at frequencies close to the linearly predicted frequency, due to resonant particle-wave inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 14 publications
2
15
0
Order By: Relevance
“…The interaction with the shear Alfén continuous spectra affects also the time evolution of the gap modes such as TAE and RSAE when they have the continuum damping and/ or the chirping frequency hits the continuum. A theoretical model of the frequency chirping of AEs with the interaction with shear Alfvén continua has been developed (Wang and Berk 2012).…”
Section: Discussion and Summarymentioning
confidence: 99%
“…The interaction with the shear Alfén continuous spectra affects also the time evolution of the gap modes such as TAE and RSAE when they have the continuum damping and/ or the chirping frequency hits the continuum. A theoretical model of the frequency chirping of AEs with the interaction with shear Alfvén continua has been developed (Wang and Berk 2012).…”
Section: Discussion and Summarymentioning
confidence: 99%
“…EP transport in velocity space occurs in 'buckets' [87], similar to 'bucket' EP transport in real space introduced in [88]. 5 Note that the original adiabatic theory of [84] has been recently extended in [85,86], but still remains local in the sense discussed in section 2.1 and hereafter. More detailed discussions of this point are given in [15,27].…”
Section: Phase Locking and Nonadiabatic Phase Space Dynamicsmentioning
confidence: 96%
“…These physics have been extensively investigated since the pioneering work of Bernstein, Greene and Kruskal (BGK) [42]; and used for analyzing nonlinear behaviors of 1D uniform Vlasov plasmas [43][44][45][46][47][48], including sources and collisional dissipation [71,79,80]. If the frequency of hole/clump pairs slowly evolves in time [81][82][83][84][85][86], it happens adiabatically at a rate ω ω | | ≪ B 2 , set by balancing the rate of energy extraction of the moving holes/clumps in the phase space with fixed background dissipation 5 . EP transport in velocity space occurs in 'buckets' [87], similar to 'bucket' EP transport in real space introduced in [88].…”
Section: Phase Locking and Nonadiabatic Phase Space Dynamicsmentioning
confidence: 99%
“…In the limit of deeply passing particles, Eqs. (11) (with h = 1) and (43) are used to find the linear dispersion relation of the mode given by…”
Section: Linear Regime the Linearized Vlasov Equation For The P-th Rementioning
confidence: 99%
“…It is shown that the square root dependency holds for the very early stages of frequency chirping. The adiabatic condition represented in subsection 3.4.2, which is implemented for the formalism, needs to be validated if it remains satisfied [23,40,43]. Eq.…”
Section: Chirping Rate Structure Evolution and Adiabaticity Validationmentioning
confidence: 99%